Akuntabilitas Pengelolaan Dana Sosial LPD Berlandaskan Budaya Tri Hita Karana - Ni Made Vita Indriyani; I Wayan Gde Yogiswara Darma Putra (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2022)
LPD is one of the institutions formed by Pakraman Village which functions to run and manage the village financial system and strives to advance the welfare of the village community and fulfill the interests of the Pakraman traditional village community itself. In carrying out its main activities, namely channeling and collecting funds, LPD Susut Kaja and LPD Desa Pekraman Kebon Bangli also carry out their accountability based on the tri hita karana culture. In LPD, the term CSR is not used, but the concept of managing social funds has a similar concept to CSR. The results obtained in this study that the management of social funds of 5% of current profit in one year period is managed according to the tri hita karana culture. Where, from 5% of the current profit is used to harmonize relationships with God through yadnya in the form of punia funds, harmonize relationships with humans in the form of basic food assistance and education and harmonize relationships with the environment in the form of providing facilities and infrastructure to preserve the environment.